2013
DOI: 10.3329/bjar.v38i3.16978
|View full text |Cite
|
Sign up to set email alerts
|

Correlation and path analysis of durum wheat (Triticum turgidum L. Var. Durum)

Abstract: A study was conducted to examine relationship between important traits of durum wheat and their direct and indirect effects on grain yield. Research work was conducted during the winter season of 2009-10 under irrigated optimum seeding condition at Regional Agricultural Research Station, Bangladesh Agricultural Research Institute, Ishurdi, Pabna with 10 advanced genotypes. A wheat variety was used as check. Positive and significant correlation was found for plant height, spikes/m 2 , and 1000-grain weight with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
10
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 5 publications
7
10
1
Order By: Relevance
“…The residual effect value was showed very low (0.0352), thus, indicated majority factors influencing the grain yield was considered in the present study. The present findings are in confirmation with Poor et al, [11], Khan et al [12] and Singh et al, [10].…”
Section: Path Analysissupporting
confidence: 93%
See 2 more Smart Citations
“…The residual effect value was showed very low (0.0352), thus, indicated majority factors influencing the grain yield was considered in the present study. The present findings are in confirmation with Poor et al, [11], Khan et al [12] and Singh et al, [10].…”
Section: Path Analysissupporting
confidence: 93%
“…Thus, indicates majority factors influencing the grain yield was considered in the present study. The present findings are in confirmation with Poor et al, [11], Khan et al [12] and Singh et al, [10]. (Table 5) revealed that Direct and indirect effect for various traits on grain yield revealed that test weight registered highest positive direct effect on grain yield (1.0335) followed by weight of grains/spike (0.1081) and spike length (0.1065).…”
Section: Path Analysissupporting
confidence: 92%
See 1 more Smart Citation
“…The genotypes with maximum value for plant height were HI 8747 (124.0 cm) followed by PBND 1625 (111.67 cm) and lowest was found in GW 1297 (78.33 cm). Since the ideal plant height ranges from 90 to 100 cm (Khan et al, 2013). Kahrizi et al, (2010) conducted studies on 18 experimental durum wheat and two checks under rain-fed condition to estimate the genetic variability parameters and relationship among 11 agrophysiological traits and results revealed that the plant height ranged from 52.70 to 96.05 cm and it had a positive significant effect on yield components.…”
Section: Resultsmentioning
confidence: 99%
“…Obsa (2014) and Awale et al (2013) also reported considerable genetic variability for grain yield and its component characters in studied bread wheat genotypes in Ethiopia. Other authors also reported considerable genetic variability for grain yield and its component characters in durum wheat (Khan et al, 2013;Mohammed et al, 2011). Gezahegn et al (2015) reported highly significant and significant differences among genotypes (P<0.01) for days to heading, days to maturity, grain filling period, 1000 kernel weight, plant height, spike length, number of productive tillers per plant, number of spikelet's per spike and number of grains per plant, grain yield per plot, harvest index and hectoliter weight.…”
Section: Analysis Of Variance Of Studied Traitsmentioning
confidence: 93%